Sensory and motor development in children at Hogar Santa Marianita. Ambato, Ecuador - Roberto Enrique Alvarado; Marìa Fernanda Morales Gòmez de la Torre; Greta Marisol Vallejo Ordoñez; Elizabeth Germania Vilema Vizuete (Medisur, 2023)
Foundation: the growing increase of abandoned children is a complex phenomenon of worldwide relevance observed in many countries and that affects various sectors of society, including health. Objective: to identify sensory and motor development difficulties in the Hogar Santa Marianita’s children. Methods: descriptive and cross-sectional study, carried out from January the 1st to June 30th, 2022 in the Huachi Chico Parish, Ambato, Ecuador. 40 children, aged from three to 60 months was the population selected. The Denver development test was used to gather information. It assesses four development areas: personal-social, fine - adaptive motor, language and large motor. Results: in children from three to 24 months old, language turned out to be the most difficult with 60%. In the group from 36 to 48 months old the fine motor areas - adaptive and personal social with 60% were more complex and in children from 49 to 60 months old the motor area with 55%. Regarding the normal/advanced development in each area, 57.5% and 55% were obtained in the motor and fine- adaptive motor areas and in the language and social personal areas 62.5% and 75%, respectively. Conclusions: the children of the Santa Marianita home need adequate early stimulation to help them adopt healthy habits that last over time and promote a better quality of life.